Ex libris M. L. Boczara / Zofia Horodyńska-Waśkowska. - Horodyńska, Zofia (1913-1944) ([wydawca nieznany], 1941)
Żaglówka płynąca po morzu, u góry mewa i napis: Ex libris, u dołu ryba i napis: M. L. Boczara.